Study on Water Quality Parameters of UTHM Campus Pagoh Drainage Water : COD, pH and Turbidity - Nordin, Mohamad Asraf; Mohmad Nor, Norasyikin; Roslan, Nuranisa; Ngadiman, Norhayati (Multidisciplinary Applied Research and Innovation, 2022)
Polluted water indicates harmful condition for the environment which causes adverse change. As a small community, the university campuses need a conducive surrounding from all aspects including water quality in drainage systems. Currently, the level of the water quality in UTHM Campus at Universiti Tun Hussein Onn Malaysia, Pagoh is still in questionable. This study was conducted to determine the level UTHM Campus Pagoh drainage water quality based on the physicochemical parameters such as COD, pH and turbidity which the results were further supported by Parameter Limits Standard for Sewage & Industrial Effluents based on Environmental Quality (Industrial Effluent) Regulations, 1979 (Malaysia). This study also identified the correlation of these three parameters between UTHM Campus and Shared Facilities (MPH). The water sample was collected in 4 weeks from April to May 2021. The results show the mean score of physicochemical parameters at location 1 and location 2 were 202.42 mg/L (COD High Range), 103.67 mg/L (COD Low Range), 136.65 mg/L (COD High Range) and 33.83 mg/L (COD Low Range), respectively. The mean of pH and turbidity for both locations were 7.24, 7.01, 17.89 NTU and 9.62 NTU. These results revealed that the level of COD at location 1 and location 2 exceed the limits except for COD low range at location 2 due to high oxidized organic matter in water sample. Furthermore, the COD high range was highly correlated between location 1 and location 2 except for pH and turbidity. Higher of COD value indicates higher content of organic matter in both locations. Thus, it affects the water quality in drainage water resulting unwanted smell and unpleasant campus landscape. Therefore, UTHM authorities must take responsibility in conducting alternative methods at different areas along the drain in order to prevent possible pollution points in UTHM Campus.